2009
DOI: 10.1677/erc-09-0136
|View full text |Cite
|
Sign up to set email alerts
|

Importance of gender-specific calcitonin thresholds in screening for occult sporadic medullary thyroid cancer

Abstract: Men and women differ in thyroidal C-cell mass and calcitonin secretion. This difference may have implications for the definition of calcitonin thresholds to distinguish sporadic C-cell hyperplasia from occult medullary thyroid cancer. This retrospective study examined the hypothesis that gender-specific calcitonin thresholds predict occult medullary thyroid cancer more accurately among patients with increased basal calcitonin levels than unisex thresholds. A total of 100 consecutive patients were evaluated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…In addition, sex, age, weight, increased calcium levels, and the assay itself also affect the calcitonin levels. Cross-reactivity with procalcitonin must be excluded (235 there is no description of tumors >0.5 cm and lymph node metastasis when the basal calcitonin is 30 to 60 pg/mL. A single nonstimulated calcitonin measurement may be considered in the work-up of thyroid nodules with suspicious US or cytologic findings with the above caveats taken into account.…”
Section: -Guidelines])mentioning
confidence: 99%
“…In addition, sex, age, weight, increased calcium levels, and the assay itself also affect the calcitonin levels. Cross-reactivity with procalcitonin must be excluded (235 there is no description of tumors >0.5 cm and lymph node metastasis when the basal calcitonin is 30 to 60 pg/mL. A single nonstimulated calcitonin measurement may be considered in the work-up of thyroid nodules with suspicious US or cytologic findings with the above caveats taken into account.…”
Section: -Guidelines])mentioning
confidence: 99%
“…We evaluated the measurement 23 uncertainty, the accuracy and the β-expectation limits: measurement uncertainty characterizes 24 the dispersion of the values around the true value and β-expectation tolerance limits with 25 β=0.95 are the upper and lower values in-between which each future measurements of the 1 same level has a probability of 95% to be found (10;11). We consider that the method will 2 provide accurate results if the 95% β-expectation tolerance interval at each concentration 3 level is fully included in the acceptance limits that we decided to settle at ±20% (12). 4 We checked the specificity of the assay by using 14 samples from patients treated by 5 complete thyroidectomy and irradiation.…”
Section: Validation Protocol 17mentioning
confidence: 99%
“…Whereas sporadic MTC is very unlikely in the presence of basal sCT < 10 pg/mL (9,10), serum concentration > 100 pg/mL has an excellent positive predictive value (PPV) for this tumor in the absence of any apparent cause (e.g., chronic renal failure, use of proton pump inhibitors, other known secretory tumors) (6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), and stimulation tests are not necessary in these cases. Despite the traditional cutoff value of 100 pg/mL, at least in women, PPV of 100% was reported in many series for basal sCT > 60 pg/mL (6,(8)(9)(10)(12)(13)(14)(17)(18)(19)(20)(21). In agreement with this finding, in the present study, after known causes of hypercalcitoninemia were excluded, none of the 492 patients without MTC had basal sCT > 40 pg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies reported PPV of 100% (8,10,20), many series found a value of only 25% (21), 20% (22), and 0/13 (9) in patients with elevated basal sCT, but < 100 pg/mL, who converted to levels > 100 pg/mL after stimulation. As a consequence, different cutoffs of stimulated sCT have been proposed in the literature (11)(12)(13)15,19), and this value remains undefined.…”
Section: Discussionmentioning
confidence: 99%